2015
DOI: 10.1038/srep17317
|View full text |Cite
|
Sign up to set email alerts
|

Association of SCNN1A Single Nucleotide Polymorphisms with neonatal respiratory distress syndrome

Abstract: Increasing evidence has demonstrated that lung fluid absorption disorders might be an important cause of neonatal respiratory distress syndrome (RDS) by influencing gas exchange or surfactant function. The SCNN1A gene, which encodes the α-ENaC, might predispose infants to RDS. To explore whether the single-nucleotide polymorphisms (SNPs) of SCNN1A are associated with RDS, we conducted a case-control study to investigate the RDS-associated loci in Han Chinese infants. Seven target SNPs were selected from the SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The epithelial sodium channel (ENaC) is expressed in several excretory organs such as the salivary glands, kidney, and lung [ 1 , 2 , 3 , 4 , 5 , 6 ]. There are four ENaC channel subunits, i.e., α, β, γ, and δ, in humans [ 7 ], which are encoded by four genes ( SCNN1A, SCNN1B, SCNN1G , and SCNN1D , respectively).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epithelial sodium channel (ENaC) is expressed in several excretory organs such as the salivary glands, kidney, and lung [ 1 , 2 , 3 , 4 , 5 , 6 ]. There are four ENaC channel subunits, i.e., α, β, γ, and δ, in humans [ 7 ], which are encoded by four genes ( SCNN1A, SCNN1B, SCNN1G , and SCNN1D , respectively).…”
Section: Introductionmentioning
confidence: 99%
“…SCNN1A appears to be essential in fluid transport in the lung. Genetic variants of SCNN1A were associated with the risk of neonatal respiratory distress syndrome [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has examined the relationships between maternal IL SNPs and obstetrical complications (Engel et al, 2005; Harmon et al, 2014; Moura et al, 2009; Qaddourah et al, 2014; Sowmya et al, 2014). Other studies have focused on the NICU infant's IL genotype/s and subsequent outcomes, including respiratory distress syndrome (RDS; Capasso et al, 2007; Li et al, 2015; Shen, Du, Wang, & Zeng, 2014), abnormal periventricular ultrasound findings (Dordelmann et al, 2006), and bronchopulmonary dysplasia (Yanamandra, Boggs, Loggins, & Baier, 2005). Similar to our work, which examined the relationship between maternal genotype and infant outcome, Pogliani, Muggiasca, Arrigoni, Rossi, and Zuccotti (2010) examined maternal methylenetetrahydrofolate reductase ( MTHFR ) genotypes and subsequent neonatal cerebral lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Lung tissue slices taken during autopsies of near-term and term infants who died of neonatal RDS showed that some alveoli were obviously dilated, with a large amount of lung fluid. This was in addition to an alveolar collapse from a lack of surfactant, and suggested that lung fluid absorption disorders might be an important additional cause of RDS by influencing gas exchange or surfactant function ( 486 ). In their study on 120 neonates with RDS and 129 controls, 7 newborns died despite of intensive care and surfactant replacement therapy.…”
Section: Specific Clinical Settings With Potential Significance Of Almentioning
confidence: 99%